Organic Memristors: Nanometer‐Scale Uniform Conductance Switching in Molecular Memristors (Adv. Mater. 42/2020). Issue 42 (20th October 2020) - Goswami, Sreetosh; Deb, Debalina; Tempez, Agnès; Chaigneau, Marc; Rath, Santi Prasad; Lal, Manohar; Ariando,; Williams, R. Stanley; Goswami, Sreebrata; Venkatesan, Thirumalai
Abstract : By solving a long‐standing problem of switching uniformity in organic memristors, in article number 2004370, Sreetosh Goswami, Sreebrata Goswami, Thirumalai Venkatesan, and co‐workers enable the genuine possibility of brain‐inspired electronics with molecular memristors. Most noteworthy previous attempts in this field have been on oxides. It's time to go molecular now! The molecular structure resembles a butterfly that is all set to "sit" on the brain.